Repeated vitrification/warming of human sperm gives better results than repeated slow programmable freezing - Teraporn Vutyavanich (2018)
In this study, we compared the effects of repeated freezing/thawing of human sperm by our in-house method of rapid freezing with slow programmable freezing. Sperm samples from 11 normozoospermic subjects were processed through density gradients and divided into three aliquots: non-frozen, rapid freezing and slow programmable freezing. Sperm in the rapid freezing group had better motility and viability than those in the slow freezing group (P0.01) after the first, second and third cycles of freezing/thawing, but there was no difference in morphology. In the second experiment, rapid freezing was repeated three times in 20 subjects. The samples from each thawing cycle were evaluated for DNA fragmentation using the alkaline comet assay. DNA fragmentation began to increase considerably after the second cycle of freezing/thawing, but to a level that was not clinically important. In the third experiment, rapid freezing was done repeatedly in 10 subjects, until no motile sperm were observed after thawing. The median number of repeated freezing/thawing that yielded no motile sperm was seven (range: 58, mean: 6.8). In conclusion, we demonstrated that repeated freezing/thawing of processed semen using our rapid freezing method gave better results than standard slow programmable freezing. This method can help maximize the usage of precious cryopreserved sperm samples in assisted reproduction technology. © 2012 AJA, SIMM & SJTU. All rights reserved.